Attitude of Class Teachers to Students with Autism in Inclusive Education Primary Schools - Indina Tarjiah; Istiqomah Riyanti (Department of Special Education, 2019)
This research aims to determine the attitudes of classroom teachers to autistic students in the inclusive primary schools. The method used is survey research with the population of 15 inclusive primary schools in Bekasi. The samples of this research are classroom teachers from 4 inclusive primary schools. Data collection techniques were carried out using a questionnaire. Data were analyzed using simple descriptive statistics. The results showed that 71% of the teachers have good attitudes, 29% have very good attitudes towards autistic students in inclusive primary schools in Bekasi. If the condition of this good attitude continues to be evenly distributed and comprehensive, it can make inclusive education in the city of Bekasi run well and successfully.